Upaya Pembinaan Sikap Religiusitas Pemerlu Pelayanan Kesejahteraan Sosial di Balai Perlindungan dan Rehabilitasi Sosial Remaja Dinas Sosial - Rahayu, Nikita Putri; Andriyani, Isnanita Noviya; Supandi, Supandi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the religious intervention strategies implemented by social workers in fostering the religiosity attitudes of Social Welfare Service Recipients (PPKS) at the Youth Social Protection and Rehabilitation Center, Social Service Agency of the Special Region of Yogyakarta. It addresses a gap in the literature concerning the use of religious approaches as instruments for social rehabilitation. This research employed a descriptive qualitative method involving eight informants: one social worker, two social assistants, and five PPKS participants. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using an interactive analysis model. The findings reveal that the Faith and Piety Development program, which includes initial assessments, religious education, structured worship practices, Qur'an recitation sessions, and congregational prayers, effectively enhances five dimensions of religiosity: belief, religious knowledge, spiritual experience, religious rituals, and moral consequences. Pre-test and post-test results show significant improvements in regular worship practices, memorization of prayers and short Qur'anic verses, and emotional control. The study concludes that religiosity-based development is an effective strategy for shaping the character and morality of PPKS participants, as well as for fostering a transformative rehabilitative environment.